The Columbia sourcebook of literary Taiwan - Chang, Sung-sheng, 1951-; Yeh, Michelle, 1955-; Fan, Mingru, 1964- (Columbia University Press, 2014)
This sourcebook contains more than 160 documents and writings that reflect the development of Taiwanese literature from the early modern period to the twenty-first century. Selections include seminal essays in literary debates, polemics, and other landmark events; interviews, diaries, and letters by major authors; critical and retrospective essays by influential writers, editors, and scholars; transcripts of historical speeches and conferences; literary-society manifestos and inaugural journal prefaces; and governmental policy pronouncements that have significantly influenced Taiwanese literature. These texts illuminate Asia's experience with modernization, colonialism, and postcolonialism; the character of Taiwan's Cold War and post-Cold War cultural production; gender and environmental issues; Indigenous movements; and the changes and challenges of the digital revolution. Taiwan's complex history with Dutch, Spanish, and Japanese colonization; strategic geopolitical position vis-à-vis China, Japan, and the United States; and status as a hub for the East-bound circulation of technological and popular-culture trends make the nation an excellent case study for a richer understanding of East Asian and modern global relations.